Rare case of paracaecal hernia with intussusception presenting as small bowel obstruction: case report - Kalyan Kumar, M. S.; R., Shyamsundar; Girieasan M., Sabari; Kannan, R.; Nedunchezhiyan, S. (International Surgery Journal, 2020)
Primary internal hernias are very rare in adults. They are an unusual cause of small intestinal obstruction and lead to high morbidity and mortality if left untreated. Clinical presentation of internal hernia is highly nonspecific. Imaging has limited role in diagnosing the cause of acute intestinal obstruction. Internal hernias are usually detected at laparotomy. We report a case of a 61-year-old male who presented with acute intestinal obstruction which was attributed later to a very rare type of internal hernia on exploratory laparotomy. A loop of ileum was found to enter the retroperitoneum through a hernia gate which was located lateral to the caecum and ileo ileal intussusception was noted proximal to the herniated loop. The segment of intestine was resected and anastamosed then hernial defect was closed. Paracaecal hernias are the rare type of hernias in internal hernia. In our case, intussusception was noted proximal to the herniated ileal loop which is a very rare presentation. Intussusception was reported previously with paraduodenal type. One should always keep in mind while conducting emergency laparotomy, internal hernias can be a cause for intestinal obstruction.